Standardization of organoid culture for evaluation of melanogenesis induced by UVB, UVA and visible light - Felicio Olivatti, Thaina Oliveira [UNESP]; Alcantara, Giovana Piteri [UNESP]; Cavalcante Esposito Lemos, Ana Claudia [UNESP]; Silva, Marcia Guimaraes da [UNESP]; Miot, Helio Amante [UNESP] (Elsevier B.V., 2020)
Background: Organoid cultures are primary cultures that maintain architectural characteristics and the relationships between cells, as well as the extracellular matrix. They are alternatives for pathophysiological or therapeutic investigation rather than animal and in vitro tests. Objective: Development of a cutaneous organoid culture model, aiming at the study of radiation-induced melanogenesis. Method: A validation study, which involved biopsies of the skin of the back of the adult ear. One sample was irradiated with different doses of UVB, UVA, or visible light (VL); the other was maintained in the dark for 72 h. The viability of the tissues was evaluated from the morphological and architectural parameters of the histology, and the expression of the glyceraldehyde-3-phosphate dehydrogenase (GAPDH) gene, by real-time polymerase chain reaction (PCR). The radiation-induced melanin pigmentation was standardized according to the doses of each radiation and evaluated by digital image analysis (Fontana-Masson). Results: The primary skin culture was standardized at room temperature using DMEM medium. The doses of UVB, UVA, and VL (blue tight) that induced differential melanogenesis were: 166 mJ/cm(2), 1.524 J/cm(2), and 40 J/cm(2). The expression of the GAPHD constitutional gene did not differ between the sample of skin processed immediately after tissue collection and the sample cultured for 72 h in the standardized protocol. Study limitations: This was a preliminary study that evaluated only the viability and integrity of the melanogenic system, and the effect of the radiation alone. Conclusions: The standardized model maintained viable melanocytic function for 72 h at room temperature, allowing the investigation of melanogenesis induced by different forms of radiation. (C) 2019 Sociedade Brasileira de Dermatologia. Published by Elsevier Espana, S.L.U.
Keywords: Melanosis; Organoids; Photobiology